Comparison of Expatriation management in the West and the East: HR consultancy perspective - Pichard, Viktor Mehdi Lester Bartiar (My University, 2021)
Expatriation management is an important branch of international human resources in which companies need help from consultants. With the emergence of important new countries in the globalization process such as China or Korea, expatriation is no longer reserved for Westerners. Among the new actors, Confucian countries which foster familial values, modesty, and hard work are particularly active in their integration into the global economy. These new actors may not have the same attitude or vision of business as their Western counterparts. The goal of the thesis is to understand how expatriation consultants can serve best their Western and Eastern customers. In particular, what differences expatriation consultants should consider and address when seeking successful support for the customers from these two diverse cultural clusters. There are studies on the differences between the expatriation processes in the East and the West, but consultancy perspective has been significantly overlooked. The literature review elaborates on the Western and Eastern expatriation process and provides a short overview of the consultancy industry. Expatriate management can be divided into three main phases: pre-departure, during the assignment, and repatriation. In each of them, similarities and differences in two cultural clusters were observed. Then, empirical research explores to what extent and in what ways consultants should follow available suggestions when serving their Eastern and Western customers. A case study was conducted in 4 consultancies in expatriate management from Europe. Consultancy managers were interviewed and secondary data was collected. Based on the analysis, consultants believe that the nationality and cultural background of the expatriate or company do not have a significant influence on expatriate management. Culture may have some influence on the behavior or vision during expatriation, but the flow of work and issues involved do not change. The main explanation for such phenomenon relies on the globalization that standardized business practices. Due to high turnover in HR staff of clients, the most challenging part for consultants is working with changing HR staffs that may not share the same vision of policies as their previous peers. It involves a high level of adaptability from consultants. The industry of expatriate management is divided into three main parts: strategic consulting, immigration, and relocation. Each consultancy has a very different field of expertise but is all linked to one important topic which is compensation. The industry is characterized by coopetition rather than competition, consultancies know each other and may recommend peers for specific enquiries out of their scope. Great consultants are people who have strong compliance knowledge and good communication skills. Among all the findings some were astonishing: In the moribund context of COVID-19, consultants are optimistic about the future of their industry.
Keywords: west; east; expatriates; consultants; management culture; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business